Draft Annual Plan 1993-94 Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1993)
The Lakshadweep, an archipelago of coral islands and reefs, form the smallest Union Territory of India. There are 36 in numbers and consist of ten inhabited islands, 17 uninhabited islands and attached islets four newly formed islets and five submerged reefs. There are several peculiar problems in the Union Territory. The fragile ecology of the coral atolls make environmental compatibility overriding consideration in Planning dispersal of population in small scattered islands far away from the mainland and separated by the turbulent Arabian Sea necessitates treatment of transport and communication as crucial factors in the developmental process.
Planning Cell Secretariat, Lakshadweep, Kavaratti